Urgensi Penerapan Etika Dalam Bisnis - Muhammad Birusman Nuryadin (Al-Tijary, 2015)
A Business ethics is a valuable learning and becomes a supplies for a person who had studied it when he / she performs a business and also when he / she works in a company. The business ethics applied in performing business has important role for a succes and eternity of that business. In the level of a knowledge, ethics is a branch of that knowledge, that is a knowledge of proper behavior. The ethics refers to compilation of morality criterions which will be a guidance to act and to perform activities. A Business is a productive activity, it’s purposes is to gain a profit. The business has a role as a fundament of economic activity, there is no economic activity without business. The profit is set through income minus expenses for service company. For trade company, the profit is set through sales minus cost of goods sold and expenses. If the business ethics is not paid ettention and also not applied in performing economics activity, a business man or business woman or who else perform economic activity will be trapped in cases of law/ norm infraction.